Tolerance In The Panginyongan Javanese Islamic Tradition: A Dialectic Of Theology, Culture, And Social Ethics - Lili Kuswanti; Moh. Roqib; Supriyanto Supriyanto (Yayasan Darusssalam Bengkulu, 2026)
This study examines the concept and manifestation of tolerance within the Panginyongan Javanese Islamic tradition as a distinctive model of culturally embedded Islam in the Banyumasan region. This study employs a qualitative approach grounded in cultural hermeneutics and the sociology of religion. Cultural hermeneutics is used to interpret meanings contained in Islamic teachings, local symbols, linguistic expressions, and communal rituals, while the sociology of religion explains the social internalization of theological values. Data were analyzed through interpretative reading, conceptual categorization, and sociological contextualization of religious and cultural sources within the Banyumasan social sphere. The findings show that tolerance in the Panginyongan Islamic tradition emerges through the interaction between Islamic normativity and local cultural values. Egalitarian language, communal rituals, functional syncretism, and ethical principles such as rukun and tepa slira translate theological concepts of mercy, justice, moderation, and non-coercion into everyday social practices. As a result, tolerance is maintained through habitual social interaction, enabling both interreligious and intra-religious differences to be managed through mutual respect and communal solidarity. This study contributes to the fields of sociology of religion and Islamic studies by showing the role of local culture in shaping practical expressions of religious tolerance.